Sotrovimab Resistance and Viral Persistence After Treatment of Immunocompromised Patients Infected With the Severe Acute Respiratory Syndrome Coronavirus 2 Omicron Variant. (22nd July 2022) - Huygens, Sammy; Oude Munnink, Bas; Gharbharan, Arvind; Koopmans, Marion; Rijnders, Bart
Abstract: Viral evolution was evaluated in 47 immunocompromised patients treated with sotrovimab. Sequencing of SARS-CoV-2 following therapy was successful in 16. Mutations associated with sotrovimab resistance were documented in 6; viral replication continued after 30 days in 5. Combination antibody therapy may be required to avoid acquired resistance in immunocompromised patients.